Voice and video conferencing fundamentals - Firestone, Scott (Cisco Press fundamentals series., 2007)
Voice and Video Conferencing Fundamentals Design, develop, select, deploy, and support advanced IP-based audio and video conferencing systems Scott Firestone, Thiya Ramalingam, Steve Fry As audio and video conferencing move rapidly into the mainstream, customers and end users are demanding unprecedented performance, reliability, scalability, and security. In Voice and Video Conferencing Fundamentals, three leading experts systematically introduce the principles, technologies, and protocols underlying today's state-of-the-art conferencing systems. Discover how to use these concepts and techniques to deliver unified, presence-enabled services that integrate voice, video, telephony, networks, and the Internet-and enable breakthrough business collaboration. The authors begin with a clear, concise overview of current voice and video conferencing, including system components, operational modes, endpoints, features, and user interactivity. Next, they illuminate conferencing architectures, offering practical insights for designing today's complex IP-based conferencing and collaboration systems. Topics covered in this book include video codecs, media control, SIP and H.323 protocols and applications, lip synchronization in video conferencing, security, and much more. Throughout the book, the authors draw on their extensive experience as Cisco® technical leaders, showing how to avoid the most common pitfalls that arise in planning, deployment, and administration. Voice and Video Conferencing Fundamentals is for every professional involved with audio or video conferencing: network and system administrators, engineers, technology managers, and Cisco solution partners alike. Whether you're involved with design, development, selection, implementation, management, or support, you'll find the in-depth knowledge you need to succeed. Scott Firestone holds a master's degree in computer science from MIT and has designed video conferencing and voice products since 1992, resulting in five patents. Thiya Ramalingam is an engineering manager for the Cisco Unified Communications organization. Thiya holds a master's degree in computer engineering and an MBA degree from San Jose State University. Steve Fry, a technical leader in the Cisco Unified Communication organization, has spent the last several years designing and developing telephony and conferencing products. Thoroughly understand the fundamentals of audio and video conferencing over IP networks Architect netw ...